Fitting Analysis of Flow Capacity of Labyrinth Weir Basedon the Length Change of Overflow Leading Edge - WANG Shangjin; QIU Yong; YANG Zewen; JIAO Xuan; ZHOU Xinyu (Renmin Zhujiang)
Even in the mountain valley reservoir, the labyrinth has a large capacity for overflowunder low head conditions, but its flow capacity decreases significantly with the increase ofweir head. Based on the existing test research results, combined with the phenomenon that theflow pattern gradually transfers from thin-walled weir flow to vacuum practical weir flow withthe increase of flow rate, this paper compares and analyzes the change of flow coefficient of W-type labyrinth weir, carries out the mathematical regression analysis on the test data by Originsoftware, gives the fitting formula of the length of the overflow leading edge of labyrinth weirdecreasing with the increase of the water head of the weir,and on this basis, obtains the fittingformulas of flow capacity of W-type and V-type labyrinth weirs based on the length change ofoverflow leading edge. The results show that the length of the overflow leading edge and the flowcapacity of the labyrinth weir change with the increase of the head.